Effect of whole body vibration on bone nanocomposites organisation and prevention of loss of bone mineral density under conditions of modeling obesity and sedentary lifestyle: experimental study - Kostyshyn , N.M.; Gzhegotskyi , M.R.; Yarova , O.A.; Kostyshyn, L.P.; Kulyk , Yu.O. (Medicni Perspektivi, 2021)
This study aimed to investigate the influence of high-frequency whole body vibration (WBV) on metabolic and structural responses of rats’ bone tissue under the sedentary lifestyle and obesity. Obesity combined with a sedentary lifestyle can present the potential negative health effects. However, whole body vibration can be used as a means of non-pharmacological correction of bone mineral density. For characterization of bone nanocomposites organisation and prevention of mineral density loss, X-ray diffraction method was used. Markers of bone remodeling in the rats’ blood: leptin, osteocalcin, tartarate resistant acid phosphatase 5b, alkaline phosphatase. Using a high-calorie diet and low-mobility model, we proved that bone mineral mass had been decreasing since 8th week. It should be noted that the decrease in the relative amount of crystalline phase (hydroxyapatite) continued throughout the experiment, up to 24 weeks (p<0.05). These structural changes were accompanied by changes in quantitative indicators of the bone remodeling markers. Rats had lower bone mineral density compared to the animals that were on the normal diet and were additionaly affected by WBV. We observed the increase of the crystalline phase volume fraction from 84% to 93% (p<0.05) in group with additional whole body vibration and the decrease of the mineral component in rats with limited mobility and high-calorie diet. Therefore, WBV could improve structural conditions of bone and prevent fat accumulation and obesity-associated biochemical markers in obese rats. This can be an effective method to improve the structural and functional state of the bones while preventing the loss of bone mineral density.